Naskah Donga Slamet Dan Reformisme Orang Jawa - Kiptiyah, Siti Mariatul (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2020)
The focus of this article is to discuss a Donga Slamet manuscript collection of Dewantara Kirti Griya Museum, in Yogyakarta. The manuscript contains the text of prayer for safety in the world and the hereafter and responds to the practice of slametan in the community. The question inscribed are; How does the text discuss slametan? How does the Donga Slamet text reproduce the new meaning of the Arabic congratulatory text into Javanese language and script? This paper is reviewed in philology. The results of this study indicate that the text of Donga Slamet was inspired by the spirit of reformism so that the meaning production of the prayer text is very rational and closes the interpretation space on slametan rituals as part of Islamic prayer practices.Keywords: prayer, Javanese Muslim, reformism, slametan.Fokus artikel ini adalah membahas sebuah manuskrip berjudul Donga Slamet koleksi Museum Dewantara Kirti Griya, Yogyakarta. Naskah tersebut memuat teks doa memohon keselamatan di dunia dan akhirat dan merespon praktik slametan di masyarakat. Pertanyaan yang didiskusikan adalah bagaimana naskah tersebut membicarakan slametan? Bagaimana naskah Donga Slamet mereproduksi makna baru atas teks doa selamat yang berbahasa Arab ke dalam bahasa dan aksara Jawa? Tulisan ini dikaji secara filologi. Hasil penelitian ini menunjukkan bahwa naskah Donga Slamet diilhami oleh semangat reformisme sehingga produksi makna teks doa selamat yang dihasilkan sangat rasional dan menutup ruang penafsiraan terhadap ritual slametan sebagai bagian dari praktik doa yang Islami.Kata kunci: doa, Muslim Jawa, reformisme, slametan